Pharmacokinetics, Pharmacodynamics, Safety and Immunogenicity of CMAB807, a New Denosumab Biosimilar, in Healthy Chinese Subjects - Chen, Hanjing; Chen, Weili; Yuan, Fei; Guo, Qingcheng; Zhang, Xunmin; Wang, Chenguang; Li, Xuening (Frontiers in Pharmacology, 2022)
Objective: Pharmacokinetics (PK), pharmacodynamics (PD), safety and immunogenicity studies were conducted to evaluate the bioequivalence of CMAB807, a biosimilar to denosumab (Prolia®), which is the only approved RANKL inhibitor for the treatment of osteoporosis. Methods: In this randomized, double-blind, single-dose phase I study, 132 healthy Chinese male subjects received a subcutaneous injection of 60 mg of CMAB807 or denosumab at a 1:1 ratio. The PK, PD, safety and immunogenicity results were assessed prior to and up to 126 days after administration. Results: The PK profiles of CMAB807 and denosumab were similar. The geometric mean ratios of the maximum concentration (Cmax), AUC0-t and AUCo-∞ were 102.41, 104.15 and 103.89%, respectively, and the 90% confidence interval was observed to be within 80.00–125.00%, which indicated the bioequivalence of CMAB807 and denosumab. The PD profiles of the two groups were also comparable. The production of the C-terminal cross-linking telopeptide of type I collagen (CTX1) was inhibited by up to 85% for 10 days, and this inhibition was sustained for up to 126 days in both the CMAB807 and denosumab groups. No subjects in the CMAB807 group, three subjects in the denosumab group before administration, and two subjects in the denosumab group after administration were positive for anti-drug antibody (ADA). Adverse events (AEs) were observed in 98.5% of subjects in both groups. The most common AE recorded was increased parathyroid hormone (PTH) levels, with incidences of 92.4 and 95.5% in the CMAB807 and denosumab groups, respectively. No clinically meaningful differences were observed in safety and immunogenicity between CMAB807 and denosumab. Conclusion: CMAB807 represents a new potential treatment option for patients with osteoporosis. Clinical Trial Registration:https://clinicaltrials.gov (Registration No. NCT03925051), http://www.chinadrugtrial/org.cn/index.html (Registration No. CTR20190800).